Low cost high accuracy parabolic troughs construction and evaluation - Kalogirou, Soteris A.; Eleftheriou, Polyvios; Lloyd, Stephen J.; Ward, John Paul (My University, 1994)
This paper describes a low cost method for mass-production of parabolic surfaces with fibreglass. Cavities produced with plastic conduits, covered with fibreglass at the back of the collector surface, provide reinforcement in the longitudinal and transverse directions, to increase rigidity. This produces a low-cost high-rigidity structure that is an accurate copy of the mould. The accuracy of the parabolic surface depends on the accuracy of the mould. The details of the mould production and the procedure for producing the parabolic surface are presented. The total thickness of the fibreglass is 4mm (mean value). The inside surface where the reflector is fixed is manufactured to a high degree of surface finish. The cost of the surface is US$ 30 per square metre of aperture area for 90° rim angle. The standard deviation of the distribution of the parabolic surface errors is found equal to 4.7 mrad which indicates a very accurate surface. The deflection of the surface to a force corresponding to a wind velocity of 90 MPH is well within reasonable limits.
Keywords: Parabolic Trough; Fibreglass parabolic castings